Minimal Change in Cardiac Index With Increasing PEEP in Pediatric Acute Respiratory Distress Syndrome - Virk, Manpreet K.; Hotz, Justin C.; Wong, Wendy; Khemani, Robinder G.; Newth, Christopher J. L.; Ross, Patrick A. (Frontiers in Pediatrics, 2019)
Objective: To determine if increasing positive end expiratory pressure (PEEP) leads to a change in cardiac index in children with Pediatric Acute Respiratory Distress Syndrome ranging from mild to severe. Design: Prospective interventional study. Setting: Multidisciplinary Pediatric Intensive Care Unit in a University teaching hospital. Patients: Fifteen intubated children (5 females, 10 males) with a median age of 72 months (IQR 11, 132) and a median weight of 19.3 kg (IQR 7.5, 53.6) with a severity of Pediatric Acute Respiratory Distress Syndrome that ranged from mild to severe with a median lung injury score of 2.3 (IQR 2.0, 2.7). Measurements: Cardiac index (CI) and stroke volume (SV) were measured on baseline ventilator settings and subsequently with a PEEP 4 cmH2O higher than baseline. Change in CI and SV from baseline values was evaluated using Wilcoxon signed rank test. Results: A total of 19 paired measurements obtained. The median baseline PEEP was 8 cmH2O (IQR 8, 10) Range 6–14 cmH2O. There was no significant change in cardiac index or stroke volume with change in PEEP. Baseline median CI 4.4 L/min/m2 (IQR 3.4, 4.8) and PEEP 4 higher median CI of 4.3 L/min/m2 (IQR 3.6, 4.8), p = 0.65. Baseline median SV 26 ml (IQR 13, 44) and at PEEP 4 higher median SV 34 ml (IQR 12, 44) p = 0.63. Conclusion: There is no significant change in cardiac index or stroke volume with increasing PEEP by 4 cmH2O in a population of children with mild to severe PARDS. Clinical Trial Registration: The study is registered on Clinical trails.gov under the Identifier: NCT02354365.